Redescription of the poorly known Allopodoiulus schioedtei (Verhoeff, 1898) and the identity of Xestoiulus luteus (Attems, 1951) (Diplopoda: Julida: Julidae) - Antić, Dragan; Stojanović, Dalibor; Šević, Mirko; Akkari, Nesrine (Zootaxa, 2024)
Based on old type material and freshly collected specimens, we evaluate and clarify the taxonomic status of two poorly known Balkan species, Allopodoiulus schioedtei (Verhoeff, 1898) and Xestoiulus luteus (Attems, 1951), and propose their synonymy with X. luteus syn. nov. as a junior subjective synonym. A lectotype is designated for A. schioedtei. In addition, the genus Allopodoiulus Verhoeff, 1898 and the species A. schioedtei are diagnosed and redescribed. The validity of the genus Allopodoiulus and the relationships of its two known species, A. schioedtei and Allopodoiulus verhoeffi (Jawłowski, 1931), are briefly discussed. A distribution map of A. schioedtei is presented.